Preparation method of micron-sized spherical silver-coated copper powder for electronic industry
After the reaction of copper sulfate and ethanol, copper oxalate precipitate is formed, and the precipitate is coated with silver nitrate solution and ammonium oxalate solution, combined with vacuum drying and kneading treatment, and finally heat treatment is carried out in a vacuum heating furnace, which is solved. In the art, there are problems such as easy oxidation of copper powder, long preparation period and poor silver plating effect, and micron-scale spherical silver-clad copper powder with strong oxidation resistance and high yield were prepared.
Patent Information
- Application Number
- CN202411577058.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-06
AI Technical Summary
When preparing micron-scale spherical silver-clad copper powder, the prior art faces the problems of easy oxidation of copper powder, long preparation period and poor silver plating effect.
After reacting with copper sulfate solution and ethanol, ammonium oxalate solution is added to form copper oxalate precipitate, and then the copper oxalate precipitate is coated with silver nitrate solution and ammonium oxalate solution. After vacuum drying and vacuum kneading, the heat treatment is finally carried out in a vacuum heating furnace. Get spherical silver-clad copper powder.
The micron-scale spherical silver-clad copper powder prepared has strong antioxidant ability, short process cycles, high yields, and avoids complex steps and local defects in traditional methods.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials, and in particular relates to a method for preparing micron-grade spherical silver-coated copper powder for the electronics industry. Background Art
[0002] With the rise in silver prices, the application cost of traditional micron-sized spherical silver powder and flaky silver powder has increased. Especially for electromagnetic shielding paint, shielding film and other shielding, conductive / antistatic fields where the application environment is not very harsh, silver-coated copper powder can be considered to overcome the defects of copper powder being easily oxidized and the problems of silver powder being expensive and easy to migrate. In other words, in addition to using pure silver powder as a conductive and thermal conductive interface material in high-reliability electronic components, the fillers used in ordinary general conductive materials (such as conductive adhesives) can be selected from silver-coated copper, silver-coated nickel, and silver-coated iron powder. Since silver and copper belong to the same main group element and have the same face-centered cubic crystal structure, except for the large difference in their redox potentials, the conductivity and thermal conductivity of silver and copper are similar. Therefore, copper-coated powder is currently the most studied and most applied filler to replace pure silver powder.
[0003] The preparation methods of silver-coated copper powder include chemical replacement method, chemical reduction method, replacement and chemical deposition composite method and melt atomization method. Among them, the chemical replacement method is to use the characteristics that the redox potential of silver is higher than that of copper. Without adding a reducing agent, the copper powder is directly added to the soluble silver salt. The copper on the surface of the copper powder continuously loses electrons and becomes ions to enter the solution. The silver ions in the solution obtain electrons and then deposit and adsorb on the surface of the copper powder to obtain silver-coated copper powder. The chemical reduction method is to use an external chemical reducing agent such as ascorbic acid, formaldehyde, etc. to reduce the silver ions into silver atoms and deposit them on the surface of the copper powder to obtain a silver layer. The replacement-chemical deposition method is a combination of the above two methods, that is, it includes silver replacement of copper and the presence of a reducing agent to reduce silver atoms to form a silver coating layer. The atomization method is to disperse the copper powder in a soluble silver salt and decompose the silver nitrate by high temperature after atomization to obtain silver, and the silver forms a coating layer on the original copper powder surface.
[0004] The traditional method for preparing silver-coated copper powder is to first use a reducing agent to prepare monovalent copper from divalent copper, and then adjust the reduction conditions to reduce the monovalent copper to obtain copper powder. Since copper powder is easily oxidized in the air, the reduction needs to be carried out under nitrogen protection, and the process is relatively cumbersome. If the physical atomization method is used to prepare the precursor copper powder, the copper powder needs to be melted into a liquid and then the liquid copper melt is atomized and cooled through a high-speed nozzle to obtain the copper powder. Practice has shown that the copper powder prepared by this method has a wide particle size distribution, the surface of the copper powder is too smooth, there is a lack of active points on its surface, the silver plating effect is poor, and the preparation cycle is long. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing micron-sized spherical silver-coated copper powder for the electronic industry. The micron-sized spherical silver-coated copper powder for the electronic industry prepared by the preparation method has strong antioxidant ability, short process cycle and high yield.
[0006] The initial oxidation temperature and the final oxidation temperature are 240-250° C. and 430-440° C. respectively, the weight gain is 4.3%-4.8%, and the yield is high.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing micron-sized spherical silver-coated copper powder for the electronics industry, the preparation method comprising the following steps:
[0009] Step S1, reacting a copper sulfate solution and ethanol at a temperature of 25-30° C. to obtain a first solution; then adding an ammonium oxalate solution to the first solution at a rate of 0.4-0.6 L / min to obtain a slurry containing white copper oxalate precipitate;
[0010] In step S1, the volume ratio of the copper sulfate solution, ethanol and ammonium oxalate solution is 8-12:1:3-7;
[0011] Step S2, adding the silver nitrate solution and the ammonium oxalate solution to the slurry at a flow rate of 15 to 25 ml / min, stirring for 25 to 35 minutes, and then standing to obtain a copper oxalate precipitate with the surface coated with silver oxalate, and then vacuum drying at 50 to 60° C. for 10 to 14 hours to obtain an oxalate precursor precipitate;
[0012] In step S2, the volume ratio of the silver nitrate solution, the ammonium oxalate solution and the slurry is 1:1:2-5;
[0013] Step S3, after mixing the oxalate precursor precipitate and stearic acid, performing a first vacuum kneading for 1.8 to 2.8 hours, adding fumed silica particles, and performing a second vacuum kneading for 1.8 to 2.8 hours to obtain a powder;
[0014] In the step S3, the mass ratio of the oxalate precursor precipitate, stearic acid and fumed silica particles is 190-195:1:15-25;
[0015] Step S4, after the powder after the second vacuum kneading is placed in a graphite crucible, it is placed in a vacuum heating furnace, and under vacuum conditions, the temperature is raised to 135-145° C. at a rate of 10-20° C. / min, and after being kept warm for 1.5-2.5 hours, the temperature is further raised to 270-320° C. at a rate of 10-20° C. / min, and after being kept warm for 1.5-2.5 hours, the powder is cooled to room temperature with the furnace under vacuum conditions, and then pickled, filtered, washed, dried and sieved in sequence to obtain spherical silver-coated copper powder.
[0016] Furthermore, in step S1, the molar concentration of the copper sulfate solution is 0.6-0.8 mol / L; the molar concentration of the ammonium oxalate solution is 0.7-0.9 mol / L.
[0017] Furthermore, in the step S1, the reaction time is 30 to 100 minutes.
[0018] Furthermore, in step S2, the molar concentration of the silver nitrate solution is 0.4-0.6 mol / L; the molar concentration of the ammonium oxalate solution is 0.23-0.29 mol / L.
[0019] Furthermore, in step S2, the standing time is 20 to 60 minutes;
[0020] In the step S2, the vacuum degree of the vacuum drying is 0.015-0.03Mpa.
[0021] Furthermore, in step S3, the fumed silica is nano-scale silicon oxide particles; the particle size of the nano-scale silicon oxide particles is 1 to 100 nm.
[0022] Furthermore, in the step S3, the vacuum degree of the first vacuum kneading is 0.015-0.03Mpa;
[0023] In the step S3, the vacuum degree of the second vacuum kneading is 0.015-0.03Mpa.
[0024] Furthermore, in step S4, the pickling solution includes polyvinyl pyrrolidone and hydrofluoric acid; the mass concentration of the hydrofluoric acid is 10-20%;
[0025] Add 1.1 to 1.5 g of polyvinyl pyrrolidone per liter of hydrofluoric acid.
[0026] Furthermore, in the step S4, the vacuum degree of the vacuum state is 0.015-0.03Mpa;
[0027] In the step S4, the drying temperature is 60 to 80° C. and the drying time is 10 to 20 hours.
[0028] Furthermore, in step S4, washing is performed until the conductivity is less than 10 microSiemens.
[0029] In summary, the solution proposed by the present invention has the following technical effects:
[0030] The present invention utilizes nano-scale silicon oxide particles (i.e., fumed silicon dioxide) whose particle size is much smaller than that of oxalate precursor particles. Under the action of a kneader, the fumed silicon dioxide particles adhere to the surface of the oily oxalate precursor to form a coating barrier layer, thereby preventing sintering after the formation of metallic silver in the late stage of thermal decomposition. The silicon dioxide particles are effectively washed away by hydrofluoric acid to obtain pure spherical silver-coated copper powder particles. The silver-coated copper powder particles of the present invention have strong oxidation resistance, and the interface bonding between silver and copper belongs to coherent / semi-coherent alloy contact, which has strong oxidation resistance and mechanical strength. The invention adopts the conventional copper powder preparation and copper powder chemical silver plating scheme, avoids the conventional steps of acid washing, alkali washing, tin chloride sensitization, palladium nitrate activation, chemical silver plating and local defects caused by poor coating. The micron-sized spherical silver-coated copper powder for the electronic industry of the invention has high oxidation resistance, can be prepared without complicated equipment and reagents, has a short process and controlled particle size. The starting oxidation temperature and the ending oxidation temperature of the micron-sized spherical silver-coated copper powder for the electronic industry of the invention are 240-250° C. and 430-440° C. respectively, the weight gain is 4.3%-4.8%, and the yield is high. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Embodiment 1:
[0033] Step S1, reacting a copper sulfate solution with a molar concentration of 0.7 mol / L and ethanol at a temperature of 28° C. for 65 minutes to obtain a first solution; then adding an ammonium oxalate solution with a molar concentration of 0.8 mol / L to the first solution at a rate of 0.5 L / min to obtain a slurry containing white copper oxalate precipitate.
[0034] Among them, the volume ratio of copper sulfate solution, ethanol and ammonium oxalate solution is 10:1:5.
[0035] Step S2, adding a silver nitrate solution with a molar concentration of 0.5 mol / L and an ammonium oxalate solution with a molar concentration of 0.26 mol / L to the slurry at a flow rate of 20 ml / min, stirring for 30 minutes, and then standing for 40 minutes to obtain a copper oxalate precipitate with a surface coated with silver oxalate, and then drying at 55° C. under a vacuum state of 0.025 MPa for 12 hours to obtain an oxalate precursor precipitate.
[0036] Among them, the volume ratio of silver nitrate solution, ammonium oxalate solution and slurry is 1:1:3.
[0037] Step S3, after mixing the oxalate precursor precipitate and stearic acid, perform the first vacuum kneading under a vacuum state of 0.025 MPa for 2.3 hours, add fumed silica particles with a particle size of 50 nm, and perform the second vacuum kneading under a vacuum state of 0.025 MPa for 2.3 hours to obtain powder.
[0038] Among them, the mass ratio of oxalate precursor precipitate, stearic acid and fumed silica particles is 192:1:20.
[0039] Step S4, after the powder after the second vacuum kneading is placed in a graphite crucible, it is placed in a vacuum heating furnace, and under vacuum conditions, the temperature is raised to 140°C at a rate of 15°C / min, and after being kept warm for 2 hours, the temperature is further raised to 300°C at a rate of 15°C / min, and after being kept warm for 2 hours, the powder is cooled to room temperature with the furnace under a vacuum state of 0.025Mpa, and then pickled, filtered, washed, dried and sieved in sequence to obtain spherical silver-coated copper powder.
[0040] The pickling solution includes polyvinyl pyrrolidone and hydrofluoric acid, the mass concentration of hydrofluoric acid is 15%, and 1.3g of polyvinyl pyrrolidone is added to each liter of hydrofluoric acid. Washing is performed until the conductivity is 8 micro-Siemens. The drying temperature is 70°C and the drying time is 15 hours.
[0041] Embodiment 2:
[0042] Step S1, reacting a copper sulfate solution with a molar concentration of 0.6 mol / L and ethanol at a temperature of 25° C. for 30 minutes to obtain a first solution; then adding an ammonium oxalate solution with a molar concentration of 0.7 mol / L to the first solution at a rate of 0.4 L / min to obtain a slurry containing white copper oxalate precipitate.
[0043] Among them, the volume ratio of copper sulfate solution, ethanol and ammonium oxalate solution is 8:1:3.
[0044] Step S2, adding a silver nitrate solution with a molar concentration of 0.4 mol / L and an ammonium oxalate solution with a molar concentration of 0.23 mol / L to the slurry at a flow rate of 15 ml / min, stirring for 25 minutes, and then standing for 20 minutes to obtain a copper oxalate precipitate with a surface coated with silver oxalate, and then drying at 50° C. under a vacuum state of 0.015 MPa for 10 hours to obtain an oxalate precursor precipitate.
[0045] Among them, the volume ratio of silver nitrate solution, ammonium oxalate solution and slurry is 1:1:2.
[0046] Step S3, after mixing the oxalate precursor precipitate and stearic acid, perform the first vacuum kneading under a vacuum state of 0.015 MPa for 1.8 hours, add fumed silica particles with a particle size of 1 nm, and perform the second vacuum kneading under a vacuum state of 0.015 MPa for 1.8 hours to obtain powder.
[0047] Among them, the mass ratio of oxalate precursor precipitate, stearic acid and fumed silica particles is 190:1:15.
[0048] Step S4, after the powder after the second vacuum kneading is placed in a graphite crucible, it is placed in a vacuum heating furnace, and under vacuum conditions, the temperature is raised to 135°C at a rate of 10°C / min, and after being kept warm for 1.5 hours, the temperature is further raised to 270°C at a rate of 10°C / min, and after being kept warm for 1.5 hours, the powder is cooled to room temperature with the furnace under a vacuum state of 0.015Mpa, and then pickled, filtered, washed, dried and sieved in sequence to obtain spherical silver-coated copper powder.
[0049] The pickling solution includes polyvinyl pyrrolidone and hydrofluoric acid, the mass concentration of hydrofluoric acid is 10%, and 1.1 g of polyvinyl pyrrolidone is added to each liter of hydrofluoric acid. The washing is performed until the conductivity is 9 micro-Siemens. The drying temperature is 60°C and the drying time is 10 hours.
[0050] Embodiment 3:
[0051] Step S1, reacting a copper sulfate solution with a molar concentration of 0.8 mol / L and ethanol at a temperature of 30° C. for 100 minutes to obtain a first solution; then adding an ammonium oxalate solution with a molar concentration of 0.9 mol / L to the first solution at a rate of 0.6 L / min to obtain a slurry containing white copper oxalate precipitate.
[0052] Among them, the volume ratio of copper sulfate solution, ethanol and ammonium oxalate solution is 12:1:7.
[0053] Step S2, adding a silver nitrate solution with a molar concentration of 0.6 mol / L and an ammonium oxalate solution with a molar concentration of 0.29 mol / L to the slurry at a flow rate of 25 ml / min, stirring for 35 minutes, and then standing for 60 minutes to obtain a copper oxalate precipitate with a surface coated with silver oxalate, and then drying at 60° C. under a vacuum state of 0.03 MPa for 14 hours to obtain an oxalate precursor precipitate.
[0054] Among them, the volume ratio of silver nitrate solution, ammonium oxalate solution and slurry is 1:1:5.
[0055] Step S3, after mixing the oxalate precursor precipitate and stearic acid, perform the first vacuum kneading under a vacuum state of 0.03 MPa for 2.8 hours, add fumed silica particles with a particle size of 100 nm, and perform the second vacuum kneading under a vacuum state of 0.03 MPa for 2.8 hours to obtain powder.
[0056] Among them, the mass ratio of oxalate precursor precipitate, stearic acid and fumed silica particles is 195:1:25.
[0057] Step S4, after the powder after the second vacuum kneading is placed in a graphite crucible, it is placed in a vacuum heating furnace, and under vacuum conditions, the temperature is raised to 145°C at a rate of 20°C / min, and after being kept warm for 2.5 hours, the temperature is further raised to 320°C at a rate of 20°C / min, and after being kept warm for 2.5 hours, the powder is cooled to room temperature with the furnace under a vacuum state of 0.03Mpa, and then pickled, filtered, washed, dried and sieved in sequence to obtain spherical silver-coated copper powder.
[0058] The pickling solution includes polyvinyl pyrrolidone and hydrofluoric acid, the mass concentration of hydrofluoric acid is 20%, and 1.5g of polyvinyl pyrrolidone is added to each liter of hydrofluoric acid. Washing is performed until the conductivity is 7 micro-Siemens. The drying temperature is 80°C and the drying time is 20 hours.
[0059] Table 1 Antioxidation Index Table of Micron-sized Spherical Silver-coated Copper Powder for Electronic Industry in Examples 1 to 3
[0060] category Initial oxidation temperature, °C End oxidation temperature ℃ Weight gain, % Example 1 249.3 439.6 4.7 Example 2 242.5 432.4 4.4 Example 3 247.7 434.6 4.8
[0061] The yields of the micron-sized spherical silver-coated copper powder for the electronic industry in Example 1, Example 2 and Example 3 are 99.5%, 99.6% and 99.7% respectively.
[0062] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing micron-sized spherical silver-coated copper powder for the electronics industry, characterized in that: The preparation method comprises the following steps: Step S1, reacting a copper sulfate solution and ethanol at a temperature of 25-30° C. to obtain a first solution; then adding an ammonium oxalate solution to the first solution at a rate of 0.4-0.6 L / min to obtain a slurry containing white copper oxalate precipitate; In step S1, the volume ratio of the copper sulfate solution, ethanol and ammonium oxalate solution is 8-12:1:3-7; Step S2, adding the silver nitrate solution and the ammonium oxalate solution to the slurry at a flow rate of 15 to 25 ml / min, stirring for 25 to 35 minutes, and then standing to obtain a copper oxalate precipitate with the surface coated with silver oxalate, and then vacuum drying at 50 to 60° C. for 10 to 14 hours to obtain an oxalate precursor precipitate; In step S2, the volume ratio of the silver nitrate solution, the ammonium oxalate solution and the slurry is 1:1:2-5; Step S3, after mixing the oxalate precursor precipitate and stearic acid, performing a first vacuum kneading for 1.8 to 2.8 hours, adding fumed silica particles, and performing a second vacuum kneading for 1.8 to 2.8 hours to obtain a powder; In the step S3, the mass ratio of the oxalate precursor precipitate, stearic acid and fumed silica particles is 190-195:1:15-25; Step S4, after the powder after the second vacuum kneading is placed in a graphite crucible, it is placed in a vacuum heating furnace, and under vacuum conditions, the temperature is raised to 135-145° C. at a rate of 10-20° C. / min, and after being kept warm for 1.5-2.5 hours, the temperature is further raised to 270-320° C. at a rate of 10-20° C. / min, and after being kept warm for 1.5-2.5 hours, the powder is cooled to room temperature with the furnace under vacuum conditions, and then pickled, filtered, washed, dried and sieved in sequence to obtain spherical silver-coated copper powder.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar concentration of the copper sulfate solution is 0.6-0.8 mol / L; the molar concentration of the ammonium oxalate solution is 0.7-0.9 mol / L.
3. The preparation method according to claim 2, characterized in that: In the step S1, the reaction time is 30 to 100 minutes.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S2, the molar concentration of the silver nitrate solution is 0.4-0.6 mol / L; the molar concentration of the ammonium oxalate solution is 0.23-0.29 mol / L.
5. The preparation method according to claim 4, characterized in that: In step S2, the standing time is 20 to 60 minutes; In the step S2, the vacuum degree of the vacuum drying is 0.015-0.03Mpa.
6. The preparation method according to claim 5, characterized in that: In the step S3, the fumed silicon dioxide is nano-scale silicon oxide particles; the particle size of the nano-scale silicon oxide particles is 1 to 100 nm.
7. The preparation method according to claim 6, characterized in that: In the step S3, the vacuum degree of the first vacuum kneading is 0.015-0.03Mpa; In the step S3, the vacuum degree of the second vacuum kneading is 0.015-0.03Mpa.
8. The preparation method according to claim 7, characterized in that: In step S4, the pickling solution includes polyvinyl pyrrolidone and hydrofluoric acid; the mass concentration of the hydrofluoric acid is 10-20%; Add 1.1 to 1.5 g of polyvinyl pyrrolidone per liter of hydrofluoric acid.
9. The preparation method according to claim 8, characterized in that: In the step S4, the vacuum degree of the vacuum state is 0.015-0.03Mpa; In the step S4, the drying temperature is 60 to 80° C. and the drying time is 10 to 20 hours.
10. The preparation method according to claim 9, characterized in that: In step S4, washing is performed until the conductivity is less than 10 microSiemens.
Citation Information
Patent Citations
Preparation method of nickel coated copper composite powder
CN103008675A
Preparation method of modified micro-granules
CN103418316A
Method for preparing nanometer spherical copper powder
CN103737013A
Process for improving structure and property uniformity of manganin sintered damping alloy
CN106424712A
Preparation method for superfine copper-silver core shell composite powder for medium-high temperature electronic slurry
CN107498064A
Cited By
Micro-nano silver coated copper conductive powder and preparation method and application thereof
CN120984877A